Karakteristik Yoghurt Probiotik dengan Penambahan Ekstrak Bunga Rosella (Hibiscus sabdariffa L) Selama Penyimpanan Suhu Dingin - Meilanie, R. T.; Arief, I. I.; Taufik, E. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2018)
Yoghurt usually made by using two types of lactic acid bacteria (LAB) is Lactobacillus bulgaricus and Streptococcus thermophilus as starters, but the bacteria are not survive in very high acid condition. In order to develop probiotics yoghurt, the addition of lactic acid bacteria (LAB) with probiotic characteristics such as Lactobacillus acidophilus, Lactobacillus casei, and Bifidobacterium is needed. Roselle flower (Hibiscus sabdariffa L) is rich in antioxidants. The addition of roselle flower extract in yoghurt is expected to improve human health. This study aims to study the effect of cold storage (2-4°C) on physical, chemical, microbiological and organoleptical characteristics of probiotic yoghurt with addition of roselle flower extract. Factorial randomized block design was used in this research. Tukey test was used as multiple range test. The results showed that there were significant interactions (P<0.05) between the types of yoghurt and time of storage to the pH value. The lowest pH value was yielded by the probiotic yoghurt with the addition of roselle flower extract. The different yoghurt types and storage time have significant effect on viscosity, total lactic acid bacteria (LAB), total titratable acidity, color and flavor.